Enhancing endometrial receptivity in FET cycles: exploring the influence of endometrial and subendometrial blood flow along with endometrial volume - Hazari, Vajihe; Sarvi, Fatemeh; Alyasin, Ashraf; Agha-Hosseini, Marzieh; Hosseinimousa, Sedigheh (Frontiers in Medicine, 2024)
Introduction Fetal health and a receptive and healthy endometrium are two essential factors in achieving successful implantation. If the endometrium is unreceptive, postponing the transfer cycle to a suitable time can enhance the chances of pregnancy. This study aims to assess the impact of endometrial and sub-endometrial blood flows measured by Doppler ultrasound, as well as endometrial volume, on endometrial receptivity in frozen embryo transfer (FET) cycles. Methods 112 patients with a mean age of 33.93 ± 4.93 years underwent in vitro fertilization (IVF). Serum β-hCG level was used to confirm pregnancy, and among the participants, 50 (44.6%) achieved pregnancy after IVF. Results The study results revealed a significant difference in endometrial blood flow between the pregnant and non-pregnant groups, with a higher pregnancy rate observed in participants exhibiting multi-focal and spare endometrial blood flows (p < 0.05). Furthermore, there was a notable association between endometrial blood flow and pregnancy outcome, as indicated by higher ongoing pregnancy rates in those with multi-focal and spare endometrial blood flows (p < 0.05). However, no significant differences were observed in endometrial variables such as volume, length, width, thickness, and pattern between the pregnant and non-pregnant groups. Additionally, contextual parameters showed no significant relationship with pregnancy outcome (p > 0.05). The study also found that endometrial measurement indices did not have a significant impact on pregnancy outcomes, with no significant differences observed between the groups (p > 0.05). Conclusion In conclusion, endometrial blood flow is crucial for a successful pregnancy after IVF, while the predictive value of the endometrial volume is limited for pregnancy outcomes.